2018
DOI: 10.3389/fcimb.2018.00204
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis Pathophysiology: Into the Storm of Cytokines

Abstract: Leptospirosis is a neglected tropical zoonosis caused by pathogenic spirochetes of the genus Leptospira. Infected reservoir animals, typically mice and rats, are asymptomatic, carry the pathogen in their renal tubules, and shed pathogenic spirochetes in their urine, contaminating the environment. Humans are accidental hosts of pathogenic Leptospira. Most human infections are mild or asymptomatic. However, 10% of human leptospirosis cases develop into severe forms, including high leptospiremia, multi-organ inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
92
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 78 publications
(117 reference statements)
2
92
0
4
Order By: Relevance
“…In contrast, IL-10 is thought to be the most important antiinflammatory cytokine which restores the immunological homeostasis in leptospirosis [10]. In addition, IL-4 and IL-13 restrict the inflammatory response [10]. The present review revealed elevated levels of the above-mentioned anti-inflammatory cytokines among leptospirosis patients and patients with complicated disease.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In contrast, IL-10 is thought to be the most important antiinflammatory cytokine which restores the immunological homeostasis in leptospirosis [10]. In addition, IL-4 and IL-13 restrict the inflammatory response [10]. The present review revealed elevated levels of the above-mentioned anti-inflammatory cytokines among leptospirosis patients and patients with complicated disease.…”
Section: Discussionmentioning
confidence: 55%
“…Failure to measure soluble TNF receptor-1 (sTNFR1) might have led to low levels of TNF-α in some studies, as the bound TNF-α will not be included in the analysis [37]. IL-1β, IL-6 and TNF-α were proposed to be pro-inflammatory cytokines which enhance the inflammatory response in leptospirosis [10]. However, the present review found IL-1β to be low among leptospirosis patients, IL-6 to be elevated and TNF-α to be equivocal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matsui et al (25,26) showed that there was a delay in the expression of the proinflammatory cytokines interleukin 1␤ (IL-1␤), IL-6, and tumor necrosis factor alpha (TNF-␣) and the chemokines CXCL10/IP-1 and CCL3/MIP-1␣ and that a massive overexpression in Leptospira-infected hamsters contrasted with that strictly regulated in mice (asymptomatic carriers). The expression of the antiinflammatory cytokine IL-10 was earlier and greater in mice than in hamsters (27). These findings indicated that in the early stage of Leptospira infection, the hamsters delayed production of cytokines, failed to activate lymphocytes and neutrophils, and allowed leptospires to escape from the host of the immune system.…”
Section: Discussionmentioning
confidence: 85%